1980
DOI: 10.1080/15287398009529867
|View full text |Cite
|
Sign up to set email alerts
|

Weak estrogenic activity of lindane in rats

Abstract: Administration of lindane (20 mg/kg . d) for 30 d to ovariectomized rats caused no significant change in the weight of the uterus, cervix, or vagina. Histological changes in these organs were comparable to those in ovariectomized control rats. Treatment with estradiol dipropionate alone and in combination with lindane induced a significant increase in the weights of these organs. Microscopically, these organs appeared normal. Lindane induced a significant increase in the glycogen content of the uterus, cervix,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
2
2

Year Published

1988
1988
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 13 publications
1
7
2
2
Order By: Relevance
“…Here, the former two showed similar strong antiestrogenicity with an EC 50 of 4.71 Â 10 À 7 and 4.03 Â 10 À 7 mol/L, respectively, which is consistent with the report that they had similar treatment efficacies in breast cancer (Howell et al, 2004). HCH performed as a weak ER antagonist in the recombinant yeast (EC 50 ¼4.60 Â 10 À 5 mol/L), although both its estrogenic and antiestrogenic activities have been observed in other organisms (Briz et al, 2011;Chadwick et al, 1988;Huang et al, 2006;Raizada et al, 1980). Because the binding of an antiestrogen to ER cannot initiate the expression of the reporter gene lac-Z, the inhibition effect test had to be executed by simultaneously exposing the yeast cells to E2 and the tested antagonist.…”
Section: Discussionsupporting
confidence: 79%
“…Here, the former two showed similar strong antiestrogenicity with an EC 50 of 4.71 Â 10 À 7 and 4.03 Â 10 À 7 mol/L, respectively, which is consistent with the report that they had similar treatment efficacies in breast cancer (Howell et al, 2004). HCH performed as a weak ER antagonist in the recombinant yeast (EC 50 ¼4.60 Â 10 À 5 mol/L), although both its estrogenic and antiestrogenic activities have been observed in other organisms (Briz et al, 2011;Chadwick et al, 1988;Huang et al, 2006;Raizada et al, 1980). Because the binding of an antiestrogen to ER cannot initiate the expression of the reporter gene lac-Z, the inhibition effect test had to be executed by simultaneously exposing the yeast cells to E2 and the tested antagonist.…”
Section: Discussionsupporting
confidence: 79%
“…The results of administering lindane over two generations did not reveal any obvious changes in the extra endpoints for endocrine disrupting activity in any generation even at doses that manifest severe toxicity, including death, despite reports of estrogenic (Raizada et al, 1980) or antiestrogenic (Uphouse and Williams, 1989;Chadwick et al, 1988;Cooper et al, 1989) effects. In uterotrophic and Hershberger assays of lindane conducted in projects of the Ministry of the Environment, no estrogenic or antiestrogenic effects were detected; nor were any androgenic or antiandrogenic effects observed (data not shown).…”
Section: Assessment Of the Test Methodsmentioning
confidence: 99%
“…It has been reported as having estrogenic (Raizada et al, 1980) or antiestrogenic activity (U phous e and Williams , 1989;Chadwick et al, 1988;Cooper et al, 1989). Testicular damage, reduced sperm counts (Dalsenter et al, 1996), prolongation of the estrous cycle, and delayed vaginal opening (Uphouse and Williams, 1989;Chadwick et al, 1988;Cooper et al, 1989) have also been reported in rats.…”
Section: Introductionmentioning
confidence: 94%
“…0 1988 mers and metabolites have received most attention (2). Another organochlorine insecticide, y-hexachlorocyclohexane, also has adverse reproductive effects in both birds (7) and mammals (&9) and has been reported to have estrogenic activity (10). One well-recognized physiological effect of estrogenic activity in the rat is a reduction of food intake and body weight gain (11-13).…”
Section: Introductionmentioning
confidence: 98%